Programmed Intermittent Epidural Bolus (PIEB) Versus Patient-Controlled Epidural Analgesia (PCEA) with Continuous Basal Infusion for Labor Analgesia: A Meta-Analysis - Nopian Hidayat; Novita Anggraeni; Ricko Yorinda Putra (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Maintaining effective labor epidural analgesia while optimizing maternal satisfaction and minimizing drug consumption remains a key objective in obstetric anesthesia. Programmed intermittent epidural bolus (PIEB) techniques have emerged as an alternative to traditional continuous epidural infusion (CEI) combined with patient-controlled epidural analgesia (PCEA). This meta-analysis aimed to compare the efficacy, local anesthetic (LA) consumption, and maternal satisfaction between PIEB regimens (typically combined with PCEA for rescue) and PCEA regimens supplemented with a continuous basal infusion (PCEA+Basal). Methods: A systematic literature search was conducted for PubMed, EMBASE, and the Cochrane Library for randomized controlled trials (RCTs) published between January 2013 and December 2024 comparing PIEB (+/- PCEA) with PCEA+Basal for labor analgesia. Primary outcomes were hourly LA consumption, maternal satisfaction (rated as high/excellent), and need for clinician rescue analgesia (breakthrough pain). Secondary outcomes included pain scores (Visual Analog Scale - VAS), mode of delivery, duration of labor stages, motor blockade incidence, and neonatal outcomes (Apgar scores). Data were extracted from suitable studies identified through the search. A random-effects model was used for meta-analysis using RevMan software. Mean Differences (MD) or Odds Ratios (OR) with 95% Confidence Intervals (CI) were calculated. Heterogeneity was assessed using the I² statistic. Results: Five studies involving a total of 1158 parturients met the inclusion criteria. The pooled analysis indicated that PIEB regimens were associated with a trend towards lower hourly LA consumption compared to PCEA+Basal (MD: -1.2 mL/hour; 95% CI: -2.5 to 0.1; P=0.07; I²=78%), although heterogeneity was high. Maternal satisfaction rated as 'high' or 'excellent' was significantly more frequent in the PIEB group (OR: 1.85; 95% CI: 1.20 to 2.85; P=0.005; I²=35%). The need for clinician rescue analgesia was numerically lower with PIEB, but the difference did not reach statistical significance (OR: 0.70; 95% CI: 0.45 to 1.10; P=0.12; I²=45%). No significant differences were noted in VAS pain scores during established labor, mode of delivery, or Apgar scores. Incidence of motor block appeared potentially lower with PIEB regimens. Conclusion: Based on this meta-analysis, PIEB regimens appear promising for labor analgesia, potentially offering comparable efficacy to PCEA+Basal while possibly reducing local anesthetic consumption and enhancing maternal satisfaction. However, significant heterogeneity was observed for some outcomes. High-quality, large-scale RCTs directly comparing optimized PIEB+PCEA protocols with PCEA+Basal infusion are crucial to definitively establish the relative benefits and risks of these techniques.